a.
Function:
[tex]h(t)=-3t^2+12t+96[/tex]Factoring -3, we have:
[tex]\begin{gathered} h(t)=-3t^2+12t+96 \\ h(t)=-3(t^2-4t-32) \end{gathered}[/tex]Middle term facotizing the term inside parenthesis:
[tex]\begin{gathered} h(t)=-3(t^2-4t-32) \\ h(t)=-3(t-8)(t+4) \end{gathered}[/tex]This is the factored form.
b.
h(t) is the height.
When it lands on the ground, the height (h(t)) is 0, so we have:
[tex]\begin{gathered} h(t)=-3(t-8)(t+4) \\ 0=-3(t-8)(t+4) \end{gathered}[/tex]If we solve this equation for t, we get the line drone lands on the ground.
Let's do this:
[tex]\begin{gathered} -3(t-8)(t+4)=0 \\ t=8,-4 \end{gathered}[/tex]Time can't be negative, so the solution is t = 8 seconds.